Endovascular treatment of acute basilar artery occlusion: Outcomes, influencing factors and imaging characteristics from the Tama-REgistry of acute thrombectomy (TREAT) study. (April 2021) - Kaneko, Junya; Ota, Takahiro; Unemoto, Kyoko; Shigeta, Keigo; Inoue, Masato; Aoki, Rie; Jimbo, Hiroyuki; Ichijo, Masahiko; Arakawa, Hideki; Shiokawa, Yoshiaki; Hirano, Teruyuki; ,
Highlights: There was no evidence about MT for the patients with ABAO. However MT achieved a good outcome in 34% of patients with ABAO in this series. The all-cause mortality was 23%. A very high rate of recanalization (96%) was achieved by MT. Positive findings for the midbrain was significantly associated with poor outcome. Abstract: Objective: The effectiveness of mechanical thrombectomy (MT) for acute basilar artery occlusion (ABAO) remains unknown. We evaluated the feasibility, safety, and efficacy of endovascular treatment for ABAO. Methods: We retrospectively investigated patients with ABAO who underwent MT using modern stent retrievers and an aspiration device between January 2015 and March 2019 at 12 comprehensive stroke centers. Functional outcomes and 90-day mortality rates were analyzed as primary outcomes. Factors influencing outcomes were analyzed as secondary outcomes. Relationships between outcome and affected area of infarction on arrival were also analyzed. Results: Seventy-three patients were included. Good outcome (modified Rankin Scale (mRS) score 0–2) was achieved in 25/73 patients (34.2%) and the all-cause 90-day mortality rate was 23.3% (17/73). Successful recanalization (modified Thrombolysis In Cerebral Infarction grade 2b and 3) was achieved in 70/73 patients (95.9%). In univariate analyses, age, National Institutes of Health Stroke Scale score, and posterior circulation Alberta Stroke Program Early CT Score (pc-ASPECTS) differed significantly between good and poor functional outcome groups. Age and pc-ASPECTS were significantly associated with functional outcomes in the logistic regression model. Positive findings for the midbrain on diffusion-weighted imaging on pc-ASPECTS and brainstem score were significantly associated with poor outcomes. Conclusion: MT with modern devices for ABAO resulted in highly successful recanalization and good outcomes. A positive finding for the midbrain on initial imaging might predict poor outcomes. Further studies are required to confirm our results.